Morphophysiological and yield traits of soybean varieties tolerant of intercropping with maize - INDAH PERMANASARI; ENDANG SULISTYANINGSIH; BUDIASTUTI KURNIASIH; DIDIK INDRADEWA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Permanasari I, Sulistyaningsih E, Kurniasih B, Indradewa D. 2023. Morphophysiological and yield traits of soybean varieties tolerant of intercropping with maize. Biodiversitas 24: 3872-3880. Not all soybean varieties grow optimally when intercropped with maize. Previously, we identified seven varieties (i.e., "Demas 1", Dena 1", "Dena 2", "Derap 1", "Devon 1", "Devon 2", and "Wilis") and two (i.e., "Dega 1" and "Mahameru") as tolerant and intolerant of intercropping based on selection indices and yield. This research aims to determine the morphophysiological and yield traits of tolerant and intolerant soybean groups intercropped with maize. The study used a randomized complete block design with three blocks as replications, and conducted from October 2019 to February 2020. Results showed that light intensity in the intercropping system had decreased by 19.91% relative to that in the monoculture system at 7 weeks after planting. The tolerant group displayed significant gains in seed weight per plant (143.66%), total biomass (50.04%), harvest index (53.33%), total number of pods and seeds per plant (119.39% and 128.86%), leaf nitrogen uptake and content (20.83% and 6.44%), chlorophyll-a:b ratio (7.20%), and stem diameter (7.65%) than the intolerant group. Correlation analysis revealed that leaf nitrogen content showed the highest correlation and significantly contributed to seed weight per plant in the tolerant and intolerant groups. Seed weight in the tolerant group was mainly affected by morphological (total biomass and harvest index), physiological (leaf nitrogen content), and yield components (number of pods), whereas that in the intolerant group was influenced only by physiological parameters (nitrogen content). Nitrogen content was considered suitable as a selection indicator for determining the seed yield of intercropped soybean varieties. Furthermore, using soybean tolerant groups for intercropping may be a solution to increase soybean production in Indonesia.